Bisannulation of 2, 3‐Dichloro‐1, 4‐naphthoquinone with o‐Nitrophenylacetic Acid Derivatives: A Succinct Synthesis of the ABCD Ring System of Alpkinidine. Issue 16 (19th April 2013) - Buccini, Marco; Jeow, Shi Yuan; Byrne, Lindsay; Skelton, Brian W.; Nguyen, Tuan Minh; Chai, Christina L. L.; Piggott, Matthew J.
Abstract: Three bisannulation strategies have been used to rapidly construct pentacyclic benzo‐fused pyrrolo[4, 3, 2‐ mn ]acridines, similar to several biologically active natural products. The key steps involve Michael substitution of 2, 3‐dichloro‐1, 4‐naphthoquinone with o ‐nitrophenylacetic acid derivatives, followed by domino amino‐Michael substitutions/cyclisations. The most efficient of these syntheses provided a model compound (1 ) including the ABCD ring‐system of alpkinidine, in just three steps and 55 % overall yield. Abstract : An annulation strategy involving successive Michael and amino‐Michael substitution reactions of 2, 3‐dichloro‐1, 4‐naphthoquinone has been used to rapidly construct the ABCD ring system of the pyrroloacridine natural product alpkinidine.